Load Dependency of Postural Control - Kinematic and Neuromuscular Changes in Response to over and under Load Conditions - Ritzmann, Ramona (PLoS One, 2015)
INTRODUCTION: Load variation is associated with changes in joint torque and compensatory reflex activation and thus, has a considerable impact on balance control. Previous studies dealing with over (OL) and under loading (UL) used water buoyancy or additional weight with the side effects of increased friction and inertia, resulting in substantially modified test paradigms. The purpose of this study was to identify gravity-induced load dependency of postural control in comparable experimental conditions and to determine the underlying neuromuscular mechanisms. METHODS: Balance performance was recorded under normal loading (NL, 1g), UL (0.16g; 0.38g) and OL (1.8g) in monopedal stance. Center of pressure (COP) displacement and frequency distribution (low 0.15-0.5Hz (LF), medium 0.5-2Hz (MF), high 2-6Hz (HF)) as well as ankle, knee and hip joint kinematics were assessed. Soleus spinal excitability was determined by H/M-recruitment curves (H/M-ratios). RESULTS: Compared to NL, OL caused an increase in ankle joint excursion, COP HF domain and H/M-ratio. Concomitantly, hip joint excursion and COP LF decreased. Compared to NL, UL caused modulations in the opposite direction: UL decreased ankle joint excursions, COP HF and H/M-ratio. Collaterally, hip joint excursion and COP LF increased. COP was augmented both in UL and in OL compared to NL. CONCLUSION: Subjects achieved postural stability in OL and UL with greater difficulty compared to NL. Reduced postural control was accompanied by modified balance strategies and compensatory reflex activation. With increasing load, a shift from hip to ankle strategy was observed. Accompanying, COP frequency distribution shifted from LF to HF and spinal excitability was enhanced. It is suggested that in OL, augmented ankle joint torques are compensated by quick reflex-induced postural reactions in distal muscles. Contrarily, UL is associated with diminished joint torques and thus, postural equilibrium may be controlled by the proximal segments to adjust the center of gravity above the base of support.